Grupo focal e pesquisa ação: processos norteadores na construção de práticas de cuidado nas disfunções da articulação temporomandibular em uma equipe de saúde da família - Minorin, Thiago Stedile (Universidade Federal de São Carlos, 2013)
Considered as a disease with chronic character and multifactorial etiology, and with intensity and duration that may vary according to the intensity of the present factors and to the interaction between these factors, the Temporomandibular Dysfunctions (TMD) may, in extreme cases, become incapacitating, or even cause the loss of working or studying days. According to researches developed in different populations, TMD present high levels of prevalence, a fact that requires more attention from the public health authorities. The treatment to this disease is more preferentially multiprofessional, therefore, the Family Health Team is the main entrance door for the patients to have access to the brazilian public health system and is a multiprofessional team, should be adequately prepared to identify, refer and follow up the cases of TMD in their territories. The presented research intended, by the application of the focal group and research-action strategies, identify and resolve the eventual lacks of knowledge concerning the TMD, helping the team to build and organize collectively this knowledge, targeting to qualify the care offered to the patients who have TMD. The participants, professionals working in the Family Health Team, were separated in groups and each group had an heterogeneous configuration referring to TMD. As a final result of this research, a flowchart has been developed by the team, with the intention of offering a better care to possible cases of patients with TMD. This step has been executed by using the tool know as Flowchart Analyzer. To achieve this result, seven meetings and a few strategies were necessary, such as: mobile visualization technic, group dinamics, expositive activity of cientific content, and daily evaluations on the work done. In conclusion, the focal group and the research-action have shown appropriate and having enough power to identify and to fill in the blanks presented by the knowledge of the team members. In addition to that, the participation on this research has been an appropriate way to acquire important knowledge that permeate the care practices that the team offers to the patients in their territory.
Keywords: Residência multiprofissional em saúde; Saúde da família; Equipe multiprofissional; Sistema Único de Saúde (Brasil); Gestão da clínica; Cuidado em saúde; Disfunção temporomandibular; Clinical management; Health care; Tempormandibular disorders; Brazilian health system; Family health strategy; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA